CSA/SuPER - Upscaling CSA with small-scale food producers organised via VSLAs: Financing for adoption, behavioural change and resilience in rural Iringa Region, Tanzania: Factsheet midterm findings Global Challenges Programme Call 4 - Food & Business Knowledge Platform; NWO-WOTRO Science for Global Development; CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
In this CSA/SuPER research project CARE, the International Center for Tropical Agriculture (CIAT), Sokoine University of Agriculture, and Wageningen University & Research come together to investigate a new model for upscaling the adoption of climate-smart agriculture practices (CSA) practices by small-scale farmers in developing countries. CSA practices increase agricultural productivity, enhance the resilience of farmers to climate change, and, where possible, mitigate greenhouse gas emissions from agriculture. It is, however, challenging to upscale the adoption of CSA practices by small-scale farmers in developing countries. Farmers often lack agricultural and agri-business knowledge and finance to invest in CSA practices. Many of them are socially disadvantaged, extremely poor, women, and young. They are usually excluded from efforts to improve access to finance and knowledge about CSA practices. We, therefore, need new rural development models that will enhance agricultural and agri-business knowledge, provide access to finance and empower socially disadvantaged groups at the same time to upscale the adoption of CSA practices. The new model implemented by CARE in Iringa, Tanzania, and tested by the CSASuPER project bundles villages savings and loan associations (VSLAs), which provide agricultural finance with farmer field business schools (FFBSs), which deliver agricultural knowledge to groups of small-scale women farmers. The model also follows sustainable, productive, profitable, equitable and resilient, so-called SuPER, farming principles. These principles guarantee that women are not excluded and receive equal opportunities to adopt those practices.